The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/ijms24065393
|View full text |Cite
|
Sign up to set email alerts
|

A Cinnamate 4-HYDROXYLASE1 from Safflower Promotes Flavonoids Accumulation and Stimulates Antioxidant Defense System in Arabidopsis

Abstract: C4H (cinnamate 4-hydroxylase) is a pivotal gene in the phenylpropanoid pathway, which is involved in the regulation of flavonoids and lignin biosynthesis of plants. However, the molecular mechanism of C4H-induced antioxidant activity in safflower still remains to be elucidated. In this study, a CtC4H1 gene was identified from safflower with combined analysis of transcriptome and functional characterization, regulating flavonoid biosynthesis and antioxidant defense system under drought stress in Arabidopsis. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 51 publications
(61 reference statements)
0
2
0
Order By: Relevance
“…Recent studies have shown that MT reduced the toxicity of cadmium in wheat through the ascorbic acid and glutathione pathways and improved drought tolerance and photosynthesis in maize seedlings [54][55][56][57], which was further confirmed in cucumber, where MT alleviated chilling tolerance by regulating the ascorbate-glutathione cycle and photosynthetic electron flux [58]. APX contributes to the ascorbate-glutathione cycle via the conversion of H 2 O 2 to water by releasing ascorbate to MDHA, which is then converted into an MDHA reductase, DHAR, and oxidized into ascorbic acid [59].…”
Section: Discussionmentioning
confidence: 80%
“…Recent studies have shown that MT reduced the toxicity of cadmium in wheat through the ascorbic acid and glutathione pathways and improved drought tolerance and photosynthesis in maize seedlings [54][55][56][57], which was further confirmed in cucumber, where MT alleviated chilling tolerance by regulating the ascorbate-glutathione cycle and photosynthetic electron flux [58]. APX contributes to the ascorbate-glutathione cycle via the conversion of H 2 O 2 to water by releasing ascorbate to MDHA, which is then converted into an MDHA reductase, DHAR, and oxidized into ascorbic acid [59].…”
Section: Discussionmentioning
confidence: 80%
“…Other endogenous elements, such as the availability of extender (IPP) and initiator (FPP) molecules, and suitable organelles with appropriate lipid and protein structures, such as Hevea RP, could be the reason for the variance in NR length in different species [ 2 , 4 , 13 , 21 , 32 , 55 ]. Exogenous stimuli, such as light/dark period, moisture, water, nutrient availability, temperature, etc., also greatly influence the production of secondary metabolites [ 56 , 57 , 58 ], especially NR and the length of the polymers in different species [ 4 , 59 , 60 , 61 ].…”
Section: Crispr/cas9 Mutagenesis: Cpt Alone Does Not Solely Determine...mentioning
confidence: 99%
“…Safflower is mainly grown as an oil crop, it has been cultivated for use as birdseed and as a source of oil for the paint industry [ 6 , 7 ]. In some areas such as Western Europe, safflower is cultivated as a source of Safflor Yellow (SY) that is produced in the floret, and used as a natural dyestuff [ 8 ]. Safflower is valuable as an edible oil crop because it produces a large amount of oil (approx.…”
Section: Introductionmentioning
confidence: 99%